IMPLEMENTATION OF COLLABORATIVE LEARNING MODEL GROUP INVESTIGATION TYPE IN APPRECIATION PROSE FICTION SUBJECT - Hiasa, Fina (Universitas Muhammadiyah Semarang, 2021)
This study aims to determine how the application of the Collaborative Learning Type Group Investigation model can improve the quality of learning in third-semester students of the Indonesian Language Education Study Program, FKIP, Bengkulu University in the fiction prose appreciation course. The descriptive method is used in this research in order to get an overview of the extent to which the quality of learning has increased by using this learning model. This classroom action research was carried out in two cycles using test and non-test techniques at the beginning and end of cycles I and II. The learning outcomes of the first cycle showed that the students who got the A score were 6 people (17%), the B score was 17 people (49%), the C score was 12 people (25%), and the D score was 0 people (0%). While the learning outcomes of the second cycle of students who obtained an A score of 12 people (34%), a B value of 18 people (51%), a C value of 5 people (14%), and a D value of 0 people (0%) These results indicate that the indicators of success the application of the Collaborative Learning Type Group Investigation model of 30% which has not been achieved in cycle I can be achieved in cycle II. In general, it can be concluded that the application of the Collaborative Learning Type Group Investigation model in the Appreciation Prose Fiction course can improve student learning outcomes.